Arrowcryptus, a new genus of Xenoscelinae of Erotylidae from Africa - Leschen, Richard A. B.; Wegrzynowicz, Piotr (Zootaxa, 2008)
Arrowcryptus n. gen. is described for Thallis jucunda Arrow, 1936 and Arrowcryptus skelleyi, n. sp. The genus is unique among erotylids by having a dilated ovipositor with a sclerotised, hook-like gonostyle with basal setae. Arrowcryptus is placed in the subfamily Xenoscelinae based on the dicondylic meso-metaventral articulation, basal pronotal pits absent, partial externally-closed procoxal cavities, tarsomeres not strongly lobed below, and submesocoxal lines absent. Absence of stridulatory files, presence of prosternal, mesoventral, and abdominal glandular ducts, presence of submetacoxal lines, will distinguish Arrowcryptus from all members of Xenoscelinae.